Safety and efficacy of subcutaneous alpha‐tocopherol in healthy adult horses. (4th June 2020) - Donnelly, C. G.; Burns, E.; Easton‐Jones, C. A.; Katzman, S.; Stuart, R.; Cook, S. E.; Finno, C. J.
Summary: Vitamin E is essential for neuromuscular function. The primary treatment, oral supplementation with natural ('RRR') α‐tocopherol, is not effective in all horses. The objectives of this pilot study were to evaluate the safety and efficacy of a subcutaneously administered RRR‐α‐tocopherol preparation. Horses were randomly assigned in a cross‐over design to initially receive RRR‐α‐tocopherol (5000 IU/450 kg of 600 IU/mL) subcutaneously (n = 3) or orally (n = 3) or were untreated sentinels (n = 2). Tissue reactions following injection in Phase I of the study necessitated adjustment of the preparation with reduction of the RRR‐α‐tocopherol concentration to 500 IU/mL in Phase 2. Following an 8‐week washout period, horses received the reciprocal treatment route with the new preparation (5000 IU/450 kg of 500 IU/mL). Serum, CSF and muscle α‐tocopherol concentrations were determined by high‐performance liquid chromatography over a 14‐day period during each phase. Serum and CSF α‐tocopherol concentrations increased significantly postinjection only when the 500 IU/mL product was administered (P<0.0001). There was no significant difference in the muscle concentration of α‐tocopherol following either treatment. All eight horses had marked tissue reaction to subcutaneous injection, regardless of product concentration. Whilst we have demonstrated that this route may be a useful alternative to oral supplementation, the marked tissue reaction makes use of such products limited at this time to only the most refractory of cases.